G283(P) How good are we at providing breastfeeding advice?. (7th April 2014) - Moule, P; Irvine, R; Subhani, S; Khatri, S; Cleugh, F
Abstract : Introduction: England has one of the lowest breastfeeding rates in Europe. Initiation rates are 83% but within one week the rate of exclusive breastfeeding drops to 46% and by 6 months to only 1%. 1 Lay and professional support, particularly if it is multi-faceted and spans pregnancy and birth, can prolong the duration and exclusivity of breastfeeding. The most beneficial interventions to promote breastfeeding include support by skilled peers and trained professionals. This study aims to evaluate women's experiences of breastfeeding services within the North West London area. Methods and materials: Data collected using questionnaire with statistical analysis of the results and a semi structured interview technique with content analysis. Study conducted within North West Thames. Questionnaire consisted of 57 questions examining demographic, economic, psychosocial experiences, antenatal and postnatal care. Results: 50 questionnaires completed. 43/50 (86%) mothers intended to breastfeed during antenatal period, 2/50 (4%) bottlefeed, 2/50 (4%) combination of breast and bottle and 3/50 (6%) undecided. 34/50 (68%) did not feel confident that their GP could provide adequate advice and support. Of those 34, 4/34 (12%) would contact their health visitor for breastfeeding related concerns. Who they would contact for breastfeeding related questions or concerns is summarised in Figure 1. 7/50 (14%) felt pushed into a decision regarding breastfeeding, 43/50 (86%) did not, however 3 expressed that breastfeeding was "strongly" encouraged with a feeling of guilt towards bottlefeeding. 24/50 (48%) received conflicting advice from healthcare professionals at some point during the antenatal or postnatal period. 14/50 (28%) identified conflicting advice around technique specifically. Conclusion: Training healthcare staff is a key source to improve experiences as they are commonly the first port of call for mothers with breastfeeding issues. With limited healthcare resources, expectations must however be managed. With consistent advice from knowledgeable staff, breastfeeding support and experiences can be improved. Maximising support within the community was highlighted as the most appropriate and preferable route, through the use of more face to face time with health visitors but also increasing confidence with mother's own GP's.